Pancreatitis, Pannicultis, Polyarthritis- A Rare Triad! - Vaibhav Patil; Uday Sanglodkar; Mayank Jain; Joy Varghese; Venkataraman Jayanthi (Archives of Clinical Gastroenterology - Peertechz Publications, 2016)
A 51 year - old - male, consuming alcohol almost 180 ml/ day for 20 years was admitted elsewhere with vomiting for 10 days, reduced urine output for 5 days and severe epigastric pain radiating to back for 3 days. In the next 3 days he developed fever alongside with pain, swelling and redness of the lower extremities, jaundice and breathlessness on exertion.